Attenuation Measurements of the Kidney on Unenhanced CT in Ureterolithiasis - Gupta, Avinash; Regmi, Pradeep Raj; Shrestha, Suraj; Adhikati, Aayush; Yadav, Sushil Kumar; Katwal, Shailendra; Khadayat, Ramesh (Journal of Institute of Medicine Nepal, 2024)
Introduction: Urolithiasis is a common disease worldwide that affects a wide range of patients. This study evaluated the diagnostic utility of attenuation values of bilateral kidneys on unenhanced helical Computed Tomography (CT) in ureterolithiasis patients.Methods: This cross-sectional study was performed in patients with ureteric calculus referred for unenhanced helical CT of the kidney, ureter, and bladder (CT-KUB). The attenuation of the renal parenchyma in Hounsfield units (HU) was measured, and a mean attenuation value was determined for obstructed and contralateral kidneys of each patient and compared.Results: Among the 95 patients, 40 had ureteric stones on the left kidney and 55 on the right kidney. Lower average attenuation value in obstructed kidneys (on the side of the ureteric stone) was seen in 75 (78.9%) patients. 79% (N=69) of patients and 3.15% (N=3) of patients showed zero average attenuation difference.  Mean attenuation values in the upper pole, middle portion, and lower pole were 28.60 HU, 30.23 HU, and 30.59 HU for obstructed kidneys and 32.74 HU, 33.41 HU, and 31.93 HU for contralateral kidneys. Mean of mean attenuation values in the three regions were 29.81 HU for obstructed kidneys and 32.69 HU for contralateral kidneys. A significant difference of 2.88 HU was found in mean attenuation values between the obstructed kidneys and the contralateral kidneys.Conclusion: Attenuation values between the kidneys can serve as a means of differentiating between obstructed and non-obstructed kidneys in unenhanced CT KUB.